Biomechanics of sport and exercise - McGinnis, P. M. (Human Kinetics, 2013)
Third Edition. Helps students learn to appreciate the consequences of external forces, how the body generates internal forces to maintain position, and how forces create movement in physical activities. This title also offers a link to an accompanying web resource that includes all of the problems from the book, separated by chapter, and 10 sample problems.